Le polycentrisme en Île-de-France : quels impacts sur la mobilité ? - Anne Aguiléra; Laurent Proulhac (Territoire en Mouvement)
Urban polycentrism is often supposed to reduce the distance traveled and also car use. By analyzing two subcenters of the Ile-de-France region, we show that the hypothesis concerning a positive effect on distance traveled is validated for non-work purposes. In terms of transport modes the conclusion is less clear. People living in the subcenters use car less than other suburban residents but non-residents people who enter or leave the subcenters, who are more and more numerous, are mainly car users.